OPTIMAL CONTROL STRATEGY WITH DELAY IN STATE AND CONTROL VARIABLES OF TRANSMISSION OF COVID-19 PANDEMIC VIRUS. (2020) - KOURRAD, AHMED; ALABKARI, AMINE; LABRIJI, ALI; ADNAOUI, KHALID; BERRAI, IMANE EL; LAAROUSSI, ADIL EL ALAMI; LAHMIDI, FOUAD
No abstract available